Pengaruh Efektivitas Terapi Self Healing Menggunakan Energi Reiki terhadap Kecemasan Menghadapi Ujian Skripsi - Budiman Bahrien; Septi Ardianty (Psympathic : Jurnal Ilmiah Psikologi, 2017)
The educational process can become a source of stressor and anxiety, especially in the final stage of a college education (thesis exam) for students. 5 of 15 College student Health Sciences Muhammadiyah Palembang experienced acute anxiety. In addition, 19 of the 67 students in STIKes Muhammadiyah who undergo remedial thesis examination have other physical complaints. Self healing using reiki energy can be utilized to reduce the anxiety state. This study investigates the effect of self healing reiki energy on anxiety. A quasi experimental design was used with the sample of forty respondents (20=intervention, 20=control group). One Way Anova was used to test the hypothesis. The results showed that there was a significant difference of the mean score of anxiety between the intervention and the control group during the post-test. Thus, treatment of self healing with Reiki energy is quite effective in reducing anxiety levels.